Effects of pretreatment with a combination of ultrasound and γ-aminobutyric acid on polyphenol metabolites and metabolic pathways in mung bean sprouts - Wang, Lidong; Li, Xiaoqiang; Gao, Fei; Liu, Ying; Lang, Shuangjing; Wang, Changyuan (Frontiers in Nutrition, 2023)
Background Polyphenols play an important role in human nutrition, therefore, how to improve its content with innovative approach is important, and understanding the metabolic pathys is necessary. Mung beans are rich in polyphenols, which made them have physiological functions such as hypoglycemia, antioxidant, and hypotension. However, the content of polyphenols in natural mung bean is relatively low, and it needs to be increased. The methods of increasing polyphenol content in grains and beans by enrichment include physical stress, such as ultrasonic stress, hypoxia stress and ultraviolet radiation, and single exogenous substance stress, such as exogenous amino acids, exogenous sugars. But, the enrichment of polyphenols using exogenous substances in combination with physical stress is less applied. Therefore, this study innovated the use of exogenous γ-aminobutyric acid (GABA) combined with ultrasonic stress to enrich mung bean sprouts polyphenols and enhance their content. The metabolic pathways of the enrichment process were also analyzed to provide a reference for studies related to the enrichment of polyphenols. Methods Mung bean seeds were pretreated with a combination of ultrasound and GABA under different conditions. Single-factor test and response surface methodology were used for optimizing pretreatment conditions of mung bean. Effects of combined pretreatments on the polyphenols content and antioxidant activity of sprouted mung beans were investigated. Additionally, metabolites were identified, and metabolic pathways were analyzed using non-targeted metabolomics techniques. Results Optimal conditions of mung bean pretreatment were found to be 370 W for ultrasound power, 40 min for ultrasonication time, 10 mmol/L for GABA concentration, and 8 h for the soaking duration. Under these conditions, the predicted polyphenol content was found to be 4.52 mg GAE/g DW. The pretreatment of mung beans with a combination of ultrasound and exogenous GABA resulted in mung bean sprouts with enhanced polyphenol content and antioxidant activity compared to mung beans germinated without pretreatment. A significant increase in the content of six polyphenols [Genistein, (-)-Epigallocatechin, Epicatechin, Nobiletin, Naringenin, Biochanin A] in the pretreated and germinated mung beans was found, and six metabolic pathways (flavonoid biosynthesis, isoflavones biosynthesis, biosynthesis of phenylpropanoids, anthocyanin biosynthesis, biosynthesis of secondary metabolites, and metabolic pathways) were significantly activated. Conclusion The obtained results suggest that a combination of ultrasound and exogenous GABA treatment can be used to produce mung bean sprouts with enriched polyphenols content and enhanced antioxidant activity.